2021
DOI: 10.1007/s10530-021-02505-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of invasive wetland macrophytes on habitat selection and movement by freshwater turtles

Abstract: Invasive species can significantly impact native wildlife by structurally altering habitats and access to resources. Understanding how native species respond to habitat modification by invasive species can inform effective habitat restoration, avoiding inadvertent harm to species at risk. The invasive graminoids Phragmites australis australis (hereafter Phragmites) and Typha ×  glauca are increasingly dominating Nearctic wetlands, often outcompeting native vegetation. Previous research suggests that turtles ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 102 publications
1
11
0
Order By: Relevance
“…Starking‐Szymanski et al (2018) also showed larger home ranges when their juveniles were released in non‐preferred habitat, and smaller home ranges when released in preferred habitat. Similar to our observation of juveniles avoiding open water, a study by Angoh et al (2021) found Blanding's turtles avoided landscape features of their habitat that were open land, forest and open water. Therefore, it is also plausible our SMAs were small due to multiple factors.…”
Section: Discussionsupporting
confidence: 91%
“…Starking‐Szymanski et al (2018) also showed larger home ranges when their juveniles were released in non‐preferred habitat, and smaller home ranges when released in preferred habitat. Similar to our observation of juveniles avoiding open water, a study by Angoh et al (2021) found Blanding's turtles avoided landscape features of their habitat that were open land, forest and open water. Therefore, it is also plausible our SMAs were small due to multiple factors.…”
Section: Discussionsupporting
confidence: 91%
“…Although we considered season as a covariate in our analysis, the lack of data from wild populations in late summer made it challenging to accurately estimate the effect of season on body condition. In addition, the ecology and demography of Blanding's turtle populations vary geographically (Edge et al 2010, Paterson et al 2012, Ritchie 2017, Angoh et al 2021), so our results should be interpreted with caution because individual‐ (e.g., maternal effects), population‐ (e.g., density), and landscape‐level (e.g., land cover type) processes can affect conservation success of headstarted turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Average daily temperature (1981-2010) ranges from −3.6°C in January to 22.6°C in July, whereas the mean annual precipitation ranges from 750-900 mm (Environment and Natural Resources 2023). Additional information about the study site can be found in Angoh et al (2021).…”
Section: Lake Eriementioning
confidence: 99%
See 1 more Smart Citation
“…The result of these drought periods has been an significant reduction of previously productive wetlands areas that are now colonized by invasive species such as perennial pepperweed (Lepidium latifolium), poison hemlock (Conium maculatum), kochia (Kochia scoparia) and quackgrass (Elymus repens), which now dominate wetland management units and considerably reducing the energetic carrying capacity and the quality of nesting habitats [2]. Invasive species are altering the structure of the vegetation of these habitats and its functionality [3] e.g., by reducing the number of breeding ducks. Among the flood management practices to restore wetland vegetation communities are flood management rotations that include intensive grazing, mowing and chemical treatments to facilitate the restoration of wetland vegetation communities and adjacent upland habitats [4].…”
Section: Introductionmentioning
confidence: 99%